2020
DOI: 10.1037/pla0000124
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of child-centered and psychoeducational groups on disruptive behavior.

Abstract: This quantitative experimental study compared a modified group form of child-centered play therapy (CCPT) called Child-Centered Group Play Counseling (CCGPC), a psychoeducational group, and a nontherapeutic control group in an elementary school setting. Participants included second, third, and fourth graders from 7 elementary schools, who exhibited behavioral and social skills deficits. School counselors conducted the groups weekly for 8 weeks. The CCGPC groups were all conducted by a school counselor who was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meanwhile, findings were largely significant among the seven studies using an active control. Two studies were an exception to this, with one comparing group interventions (including group play counseling and psychoeducation) to participation in nontherapeutic group activities (Fry et al, 2020; n = 79, g = −0.05, p = .89) and the other comparing the friend-to-friend group therapy to an educationally based group intervention aimed at improving homework, study skills, and organization (Leff et al, 2015; n = 144, g = 0.30, p = .09). The remaining five studies reported significant results in favor of group, with effect sizes ranging from 0.58 to 1.49. compared anger management group training to a diluted anger management training using videotapes (n = 59, g = 0.58, p = .04).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, findings were largely significant among the seven studies using an active control. Two studies were an exception to this, with one comparing group interventions (including group play counseling and psychoeducation) to participation in nontherapeutic group activities (Fry et al, 2020; n = 79, g = −0.05, p = .89) and the other comparing the friend-to-friend group therapy to an educationally based group intervention aimed at improving homework, study skills, and organization (Leff et al, 2015; n = 144, g = 0.30, p = .09). The remaining five studies reported significant results in favor of group, with effect sizes ranging from 0.58 to 1.49. compared anger management group training to a diluted anger management training using videotapes (n = 59, g = 0.58, p = .04).…”
Section: Resultsmentioning
confidence: 99%
“…Another systematic review and meta-analysis revealed that school-based antibullying programs are effective in reducing bullying perpetration and victimization [18]. Other study also presented the effectiveness of child-centered and psychoeducational groups in increasing social skills [19].…”
Section: Introductionmentioning
confidence: 99%